DGK-θ: Structure, Enzymology, and Physiological Roles - Tu-Sekine, Becky; Goldschmidt, Hana L.; Raben, Daniel M. (Frontiers in Cell and Developmental Biology, 2016)
Diacylglycerol kinases (DGKs) are a family of enzymes that catalyze the ATP-dependent phosphorylation of diacylglycerol (DAG) to phosphatidic acid (PtdOH). The recognition of the importance of these enzymes has been increasing ever since it was determined that they played a role in the phosphatidylinositol (PtdIns) cycle and a number of excellent reviews have already been written (see (1-7) among others). We now know there are ten mammalian DGKs that are organized into five classes. DGK-θ is the lone member of the Type V class of DGKs and remains as one of the least studied. This review focuses on our current understanding of the structure, enzymology, regulation, and physiological roles of this DGK and suggests some future areas of research to understand this DGK isoform.